Analisis Bibliometrik Perkembangan Software Piracy Di Kalangan Masyarakat Melalui Kajian Publikasi Riset Dari Indonesia - Merry Dwi Handayani; Qoyyimil Jamilah; Aulia Hanifah; Nur Aini Rakhmawati (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
The rapid and modern development of technology has created an increasing need for adequate software, but sometimes the cost of software is often a problem for some individuals and companies who want to use it. Software piracy has become a common problem in society, which is detrimental to copyright holders and threatens the security of user data. This research analyzes publications on software piracy and its impact on Indonesian law from 2019 to 2024. The method used in this research is bibliometric analysis by collecting data through Google Scholar. The results show five main clusters covering legal aspects and internet technology. Through this analysis, it was found that the close relationship between software piracy and Law No. 11 of 2008 on Electronic Information and Transactions, Constitution No. 28 of 2014 on Copyright, Law No. 1 of 2023 on the criminal code, and Law No. 1 of 2024 on the second amendment to Law No. 11 of 2008 on Electronic Information and Transactions are very relevant in dealing with this problem. However, further analysis is needed to understand their practical implementation and effectiveness in addressing software piracy. This research shows the potential for further research in software piracy based on keywords that are rarely used in previous studies.